Urgensi Pengaturan Injunction dalam Rancangan Undang-Undang Hukum Acara Perdata - Febrilian Dame Nuraldi; Michael Sebastian Chang; I Gusti Ngurah Anom Manacika Mahawijaya (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
The concept of injunction in common law countries is similar to the concept of provision, confiscation, and provisional determination so that the concept of injunction can be used to complete the deficiencies of provision, confiscation, and provisional determination. This research examines injunction arrangements in common law countries, in this case, the United States and Singapore, which are then transplanted into Indonesian law through the Indonesian Civil Procedure Bill. The research method was carried out normatively and then explained descriptively accompanied by a prescription on how provision, confiscation, and provisional determination should be regulated in Indonesia. Arrangements for provision, confiscation, and provisional determination are still scattered in various laws and even most of the Dutch colonial legacies are used without an official translation. This condition causes legal uncertainty that can be detrimental to justice seekers. The state’s efforts in establishing a unique Indonesian civil procedural law can be seen through the Indonesian Civil Procedure Bill. This bill also contains a concept similar to an injunction. The bill, which is expected to eliminate legal uncertainty for justice seekers, still does not specify a concept similar to the injunction in Indonesia.